A Literature Review on Parental Feeding Practices and Sugar-Related Dietary Behaviors in Children and Adolescents - Annisa Alasimi, Nadina Hajar (Politeknik NEST, 2025)
The consumption of sugar-rich foods and beverages has been identified as a primary factor contributing to the rising prevalence of obesity and non-communicable diseases among children and adolescents. Food Parenting Practices (FPP) and Parental Feeding Styles (PFS) play a crucial role in shaping children’s eating behaviors from an early age. This systematic review aims to narratively synthesize FPP and PFS related to sugar-rich foods and beverages and their associations with the prospective dietary behaviors of children and adolescents based on literature from 2017 to 2023. The findings indicate that highly controlling parenting practices, such as restricting sugar intake or using sugary foods as rewards, are associated with the development of unhealthy eating behaviors and preferences for sugar-rich foods and beverages over time. Conversely, parenting practices that emphasize structure and balance in dietary choices yield more positive long-term outcomes, associated with reduced preferences for sugar-rich foods and drinks. These results underscore the importance of fostering a healthy home environment and active parental role modeling in promoting healthier dietary behaviors among children and adolescents. Evidence-based recommendations are provided for health professionals and parents to support healthy food parenting practices.